IMPROVEMENT OF THE POLLEN QUALITY AND GERMINATION LEVELS IN GRAPES (VITIS VINIFERA L.) BY LEAF PULVERIZATIONS WITH NANOSIZE CALCITE AND SEAWEED EXTRACT (ASCOPHYLLIUM NODOSUM) - A. Sabir (Journal of Animal and Plant Sciences, 2015)
Studies indicated that toxic materials such as pesticides, plant bio-stimulants and chemical fertilizers used in intensified agriculture are detrimental to the viability of the plant pollen and cause reduction in plant fertility. Pollen quantity, viability and germination capability are important parameters for both fruitfulness and breeding studies. Therefore, effects of 100% organic materials, namely nanosize calcite (CaCO3, SiO2, MgO, and Fe2O3) and seaweed extract (Ascophyllium nodosum) pulverizations on size, fertility and germination rates of the pollens of 'Thompson Seedless' and 'Narince' grapevine cultivars were investigated. The calcite treatment, alone or along with seaweed improved viable pollen (dark red) percentages that varied from 65.(control) to 77.9% (combined treatment) in 'Thompson Seedless', and from 55.3% (control) to 68.8% (calcite) in 'Narince'. The improvement of pollen germination due to calcite was more pronounced in pollens of 'Narince' than in 'Thompson Seedless'. In general, slight changes in lengths of polar and equatorial axises of grape pollens in response to the treatments were also observed. The correlation between pollen viability and germination percentages was different among the cultivars. Overall, leaf pulverizations of nanosize calcite and seaweed extract had remarkably positive effects on grapevine pollen characteristics and therefore both applications could be recommended as environmental-friendly practices in sustainable viticulture.
Keywords: Pollen quality; sustainable practices; leaf fertilizers; grapevine